Doing Right Leads to Doing Well: When the Type of CSR and Reputation Interact to Affect Consumer Evaluations of the Firm - Lii, Yuan-Shuh; Lee, Monle (2012)
This study investigates the efficacy of three corporate social responsibility (CSR) initiatives—sponsorship, cause-related marketing (CRM), and philanthropy—on consumer–company identification (C–C identification) and brand attitude and, in turn, consumer citizenship behaviors. CSR reputation is proposed as the moderating variable that affects the relationship between CSR initiatives, C–C identification, and brand attitude. A conceptual model that integrates the hypothesized relationships and the moderating effect of CSR reputation is used to frame the study. Using a between-subjects factorial designed experiment, the results showed that all three CSR initiatives have a significant effect on C–C identification and brand attitude. The level of that influence, however, varied according to a firm’s CSR reputation. Managerial implications of these findings are also discussed.
Keywords: Sponsorship; Philanthropy; Cause-related marketing; Corporate Social Responsibility; Citizenship behavior; C–C identification; Brand attitude